2014
DOI: 10.1093/aob/mcu233
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between functional traits and inorganic nitrogen acquisition among eight contrasting European grass species

Abstract: The results support the use of leaf traits, and especially SLA and LDMC, as indicators of the N uptake ability across a broad range of grass species. The difficulties associated with assessing root properties are also highlighted, as root traits were only weakly correlated with leaf traits, and only RDMC and, to a lesser extent, root N content were related to leaf traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 71 publications
5
69
1
Order By: Relevance
“…The proportion of herbs in our plant communities increased plant 15 N uptake, while a higher CWM SLA indirectly increased microbial 15 N uptake, and a higher CWM RTD decreased plant 15 N uptake. These results confirm the central role of roots in ecosystem N retention (De Vries et al ., 2012a), and corroborate findings that plants with exploitative growth strategies have the highest rates of N uptake (Grassein et al ., 2015). However, they contradict the notion (De Vries & Bardgett, 2012), and field observations (Laughlin, 2011; De Vries et al ., 2012a; Grigulis et al ., 2013), that plant communities dominated by slow‐growing, resource‐conservative species and their associated microbial communities have the greatest N retention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of herbs in our plant communities increased plant 15 N uptake, while a higher CWM SLA indirectly increased microbial 15 N uptake, and a higher CWM RTD decreased plant 15 N uptake. These results confirm the central role of roots in ecosystem N retention (De Vries et al ., 2012a), and corroborate findings that plants with exploitative growth strategies have the highest rates of N uptake (Grassein et al ., 2015). However, they contradict the notion (De Vries & Bardgett, 2012), and field observations (Laughlin, 2011; De Vries et al ., 2012a; Grigulis et al ., 2013), that plant communities dominated by slow‐growing, resource‐conservative species and their associated microbial communities have the greatest N retention.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with the findings by Grassein et al . (2015), who found that the uptake and affinity for N of individual grasses increased with exploitative leaf traits. Importantly, although herbs differed from grasses in most traits and thus affected CWM values of these traits in our mixtures, they did not differ in SLA and RTD, which were the traits that best explained plant and microbial 15 N uptake in our SEMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the length group, intermediate values of specific leaf area, specific root length, root tissue density and N concentration were observed. Based on the findings of Grassein et al (2015), species from this group would thus be expected to be more acquisitive or less conservative than the species from the biomass group. In comparison to the biomass group, the length group showed lower C/N ratio and higher P concentration that are more favorable to mineralization.…”
Section: Influence Of Plant Traits On Nutrient Uptakementioning
confidence: 99%
“…These approaches generally use the leaf economics spectrum (Wright et al 2004), where exploitative leaf traits that maximise photosynthesis, such as high specific leaf area and leaf nitrogen content, maximize plant growth and nutrient uptake, and accelerate rates of soil nutrient and carbon cycling (e.g. Fortunel et al 2009;Garnier et al 2004;Grassein et al 2015;Laughlin 2011;Orwin et al 2010). Recently, ecologists have shifted their focus from aboveground plant functional traits to belowground traits for explaining soil and ecosystem processes .…”
Section: Introductionmentioning
confidence: 99%